40Ar/39Ar-age of the Talakhtakh diatreme rocks (Arctic Siberia) - Sergey Zhmodik; Petr Ivanov; Alexey Travin; Sergey Vishnevskiy; Denis Yudin; Elena Lazareva (2021)
In the Eastern margin of the  Anabar shield the Proterozoic alkaline pipes, dikes, and stocks are widespread. The largest Talakhtakh diatreme cut Middle-Upper Riphean dolomites (MP3-NP2) at the left bank of Kuonamka River (Fig. 1). The Talakhtakh diatreme includes alkaline basaltoids, ultra-K-trachytes, lamproites, olivine leucitites, tephrites, (Vishnevsky et al., 1986). TRE distribution indicates the proximity of sanidine trachytes to lamproites.  The 40Ar/39Ar laser dating show two age maxima 1476 ± 17 (N = 14) and 1321 ± 17 (N = 9) Ma. If 10 points form a linear regression, with an age value of 1497 ± 40 million years, an initial ratio of 189 ± 100, then most of the remaining points are located along the abscissa axis. This arrangement may be associated with different degrees of rejuvenation of the K/Ar isotope system within the dating sites. The weighted average of 1476 ± 17, as more accurate, corresponds to the age of sample formation. Ernst et al (2016) identified a new Kuonamka Large Igneous Province (LIP), based on U-Pb dating of baddeleyites from dolerite dikes and sills of the Anabar shield. The age of Kuonamka LIP is ~ 1501 ± 3 Ma. The resulting 40Ar/39Ar is the age of leucite trachytes (lamproites) The Talakhtakh diatreme fully corresponds to the time of occurrence of the Kuonamka LIP and indicates the formation of high-K effusions of the Talakhtakh complex during this period. This work supported by RFBR grants: No. 18-05-70109 and the Russian Ministry of Education and Science Gusev N.I., et al. State Geological Map of the Russian Federation. Sheet R-49-Olenek. An explanatory Memorandum. Saint Petersburg: Map factory VSEGEI. . 2016. 448 с. Vishnevskiy S.A., Dolgov Yu. A., Sobolev N. V.  Geology&Geophysics, 1986. № 8. P. 17-27. Ernst R. E., Okrugin A.V. et al.  Russian Geology&Geophysics. 2016. № 5. P. 653,-671. <img src="data:image/png;base64, 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